2018
DOI: 10.1159/000484928
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Effects of Q10, Vitamin D<sub>3</sub>, and <smlcap>L</smlcap>-Arginine on Cardiac and Endothelial Cells

Abstract: This work demonstrates the cooperative effect of Q10, vitamin D3, and L-arginine on both cardiac and endothelial cells. The effects of Q10, L-arginine, and vitamin D3 alone or combined on cell viability, nitric oxide, and reactive oxygen species productions in endothelial and cardiac cells were studied. Moreover, the involvement of PI3K/Akt and ERK/MAPK pathways leading to eNOS activation as well as the involvement of vitamin D receptor were also investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…Nitric oxide (NO) production by astrocyte was assessed by indirect measurement of nitrite concentration using Griess assay (Promega Corporation, Madison, WI, USA) following the manufacturer’s instruction, as previously described [ 67 ]. The absorbance was measured by a microplate reader (VICTOR X4 multilabel plate reader, Perkin Elmer, Waltham, MA, USA) at 550 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Nitric oxide (NO) production by astrocyte was assessed by indirect measurement of nitrite concentration using Griess assay (Promega Corporation, Madison, WI, USA) following the manufacturer’s instruction, as previously described [ 67 ]. The absorbance was measured by a microplate reader (VICTOR X4 multilabel plate reader, Perkin Elmer, Waltham, MA, USA) at 550 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D can affect blood pressure through several mechanisms. Indeed, in both animals and humans it has been shown that vitamin D decreases renin-angiotensin-aldosterone system (RAAS) activity (Li et al, 2002 ; Tomaschitz et al, 2010 ), modulates endothelial function (Wong et al, 2010 ; Pittarella et al, 2015 ; Molinari et al, 2018 ) and regulates vascular oxidative stress (Argacha et al, 2011 ).…”
Section: The Antioxidant Therapy In Hypertensionmentioning
confidence: 99%
“…Beyond the above-cited experimental and clinical reports, the extensive literature discusses the potential benefits of treating ARD and mitochondria-defective diseases using MNs [ 14 , 25 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Consistent with the available database from pre-clinical and clinical investigations, the available MDF-related reviews mainly focus on the potential advantages of using individual MNs in the treatment of mitochondria-defective disorders, with the exception of the “mitochondrial cocktail” perspective proposed by Tarnopolsky [ 136 ] and as discussed in our previous review [ 137 ].…”
Section: Discussionmentioning
confidence: 99%